2020
DOI: 10.1002/ajmg.a.61528
|View full text |Cite
|
Sign up to set email alerts
|

Congenital limb reduction defects in 1.6 million births in Argentina

Abstract: The objectives of this study were to describe the birth prevalence of limb reduction defects (LRD) in Argentina, their clinical features, and to review the literature on this topic. The data source was the National Network of Congenital Anomalies of Argentina, a surveillance system that has been operative since 2009. Data were collected from November 1, 2009 to December 31, 2016. 1,663,610 births and 702 affected patients were registered during this period. The prevalence of LRD was 4.22/10,000 births (CI 95%:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The prevalence of many specific defects appeared to be consistent with the reported or accepted global prevalence, including congenital heart defects, talipes equinovarus, hypospadias, cleft lip-palate, cleft lip, cleft palate, limb reduction, anal atresia, anotia/microtia, omphalocele, and bladder exstrophy 22,[37][38][39][40][41][42][43][44][45][46][47] . However, the prevalences of some specific defects seem to be lower than the reported or accepted global prevalences, such as Table 7.…”
Section: Discussionsupporting
confidence: 77%
“…The prevalence of many specific defects appeared to be consistent with the reported or accepted global prevalence, including congenital heart defects, talipes equinovarus, hypospadias, cleft lip-palate, cleft lip, cleft palate, limb reduction, anal atresia, anotia/microtia, omphalocele, and bladder exstrophy 22,[37][38][39][40][41][42][43][44][45][46][47] . However, the prevalences of some specific defects seem to be lower than the reported or accepted global prevalences, such as Table 7.…”
Section: Discussionsupporting
confidence: 77%
“…LRDs of one limb less often have a genetic cause, compared to LRDs of multiple limbs (Cobben, Hiemstra, & Robinson, 1994; Firth & Hurst, 2017; Harper, 2010), but only few studies have substantiated this. Previous epidemiological studies regarding LRDs have reported prevalence rates (general and per subcategory), the affected side (left: right ratio), symmetry, associated malformations, and diagnoses (Alberto, Barbero, Liascovich, Bidondo, & Groisman, 2020; Bedard, Lowry, Sibbald, Crawford, & Kiefer, 2018; Bedard, Lowry, Sibbald, Kiefer, & Metcalfe, 2015; Evans, Vitez, & Czeizel, 1994; Klungsoyr et al, 2019; Koskimies, Lindfors, Gissler, Peltonen, & Nietosvaara, 2011; Vasluian et al, 2013). To our knowledge there has only been one retrospective cohort study, which analyzed diagnosis rates in patients with uni‐ versus bilateral preaxial longitudinal defects of the upper limb ( n = 119) (James, Green, McCarroll, & Manske, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Limb reduction defects are congenital anomalies characterized by the absence or severe hypoplasia of a complete or a part of a limb. The reported prevalence of congenital limb deficiency is 1 in 2000 1 . The possible causes include chromosomal anomalies, for example, Trisomy 18, monogenic syndromes, for example, Fanconi anemia, teratogens, or other environmental exposures.…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of congenital limb deficiency is 1 in 2000. 1 The possible causes include chromosomal anomalies, for example, Trisomy 18, monogenic syndromes, for example, Fanconi anemia, teratogens, or other environmental exposures. Still, the etiology is unknown in most cases.…”
Section: Introductionmentioning
confidence: 99%